A Meta-Analysis of the Therapeutic Effects of Glucagon-Like Peptide-1 Agonist in Heart Failure. (1st July 2012) - Munaf, Mohammed; Pellicori, Pierpaolo; Allgar, Victoria; Wong, Kenneth
Abstract : We conducted a meta-analysis of the existing literature of the therapeutic effects of using GLP-1 agonists to improve the metabolism of the failing heart. Animal studies showed significant improvement in markers of cardiac function, such as left ventricular ejection fraction (LVEF), with regular GLP-1 agonist infusions. In clinical trials, the potential effects of GLP-1 agonists in improving cardiac function were modest: LVEF improved by 4.4% compared to placebo (95% C.I 1.36–7.44, P = 0.005 ). However, BNP levels were not significantly altered by GLP-1 agonists in heart failure. In two trials, a modest increase in heart rate by up to 7 beats per minute was noted, but meta-analysis demonstrated this was not significant statistically. The small number of studies plus variation in the concentration and length of the regime between the trials would limit our conclusions, even though statistically, heterogeneity chi-squared tests did not reveal any significant heterogeneity in the endpoints tested. Moreover, studies in non-diabetics with heart failure yielded conflicting results. In conclusion, the use of GLP-1 agonists has at best a modest effect on ejection fraction improvement in heart failure, but there was no significant improvement in BNP levels in the meta-analysis.